College Algebra (10th Edition)

Published by Pearson
ISBN 10: 0321979478
ISBN 13: 978-0-32197-947-6

Chapter R - Section R.7 - Rational Expressions - R.7 Assess Your Understanding - Page 71: 51


$-\displaystyle \frac{(11x+2)}{(x+2)(x-2)}$

Work Step by Step

$\displaystyle \frac{x-3}{x+2}-\frac{x+4}{x-2}=... \quad LCD=(x+2)(x-2)$ $=\displaystyle \frac{(x-3)(x-2)-(x+4)(x+2)}{(x+2)(x-2)}$ $=\displaystyle \frac{x^{2}-5x+6-(x^{2}+6x+8)}{(x+2)(x-2)}$ $=\displaystyle \frac{x^{2}-5x+6-x^{2}-6x-8}{(x+2)(x-2)}$ $=\displaystyle \frac{-11x-2}{(x-4)(x+3)}$ $=\displaystyle \frac{-(11x+2)}{(x-4)(x+3)}$ $=-\displaystyle \frac{(11x+2)}{(x+2)(x-2)}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.